ANALISIS RASIO KEUANGAN BANK ACEH SYARIAH DAN BANK SYARIAH INDONESIA - Nasution, Muhammad Syafril; Shahri, Muhammad Alfi (Faculty of Islamic Economics and Business, Sultan Aji Muhammad Idris State Islamic University of Samarinda, 2025)
This study aims to analyse and compare the financial performance of Bank Aceh Syariah (BAS) and Bank Syariah Indonesia (BSI). The two banks have different structural and operational characteristics, with BAS being the first regional bank to fully convert to the sharia system, while BSI is the largest sharia bank in Indonesia, resulting from the merger of three state-owned banks. This study employs a qualitative method with a comparative approach to four key financial ratios: non-performing financing (NPF), capital adequacy ratio (CAR), liquidity ratio (FDR), and return on equity (ROE). The results indicate that BSI generally outperforms BAS in terms of financial performance. BSI demonstrates lower financing risk, stronger capitalisation, healthy liquidity, and higher profitability. Meanwhile, BAS continues to show good stability and strategic relevance in Aceh's economic development. This comparison is expected to provide insights to stakeholders in evaluating the strengths and challenges of each bank in supporting the national sharia financial system.